Analisa Pergeseran Kalender Gregorian Menjadi Kalender Dunia - Sari, Indah Puspita; Siti Tatmainul Qulub (Universitas Islam Negeri Mataram, 2022)
The Julius calendar or also known as the Old Style calendar is a calendar pioneered by Julius Caesar as a reform of the Roman republican calendar. The Julian calendar was formed at the time of knowing a difference of about 3 months in the calendar that was in effect at that time, namely the Ancient Roman Calendar which had been replaced long ago. The Ancient Roman calendar set the length of a year at only 365 days, ignoring the remaining days of the actual solar year. This is known when the day of the harvest season coincided with a holiday among the Romans which actually fell in summer but occurred in winter, where the number of days in the Roman year was shorter than the number of days in the solar year. Therefore, Julius Caesar and assisted by a Greek astronomer named Sosigenes corrected the error of the Roman calendar system at that time by making one year 365 days. Then the Gregorian calendar was born. This calender is the Gregorian calender or it can also be called the New Style Calender reformed from the Julius calender. The Gregorian calender is the most widely used calender in the western world and is the standard for calculating international days today although initially rejected by some countries.Keywords: Julius calender, Gregorian calender, Gregorian calender rejection.